2022
DOI: 10.1021/jasms.2c00252
|View full text |Cite
|
Sign up to set email alerts
|

Free Radical-Based Sequencing for Native Top-Down Mass Spectrometry

Abstract: Native top-down proteomics allows for both proteoform identification and high-order structure characterization for cellular protein complexes. Unfortunately, tandem MS-based fragmentation efficiencies for such targets are low due to an increase in analyte ion mass and the low ion charge states that characterize native MS data. Multiple fragmentation methods can be integrated in order to increase protein complex sequence coverage, but this typically requires use of specialized hardware and software. Free-radica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…In light of this issue, internal fragments (fragment ions containing neither the N nor the C terminus) have recently been incorporated into TD-MS data analysis. [13][14][15][16][17][18] The addition of internal fragments in TD-MS analysis has been shown to enhance protein sequence information, with many reports showing near complete protein sequence coverage for a range of common test proteins. 14 Further, Wei and co-workers demonstrated that the inclusion of internal fragments can be utilised to gain extensive protein structure characterisation by enabling enhanced determination of disulfide bond connectivity.…”
Section: Introductionmentioning
confidence: 99%
“…In light of this issue, internal fragments (fragment ions containing neither the N nor the C terminus) have recently been incorporated into TD-MS data analysis. [13][14][15][16][17][18] The addition of internal fragments in TD-MS analysis has been shown to enhance protein sequence information, with many reports showing near complete protein sequence coverage for a range of common test proteins. 14 Further, Wei and co-workers demonstrated that the inclusion of internal fragments can be utilised to gain extensive protein structure characterisation by enabling enhanced determination of disulfide bond connectivity.…”
Section: Introductionmentioning
confidence: 99%